New device for nonvolitional evaluation of quadriceps force in ventilated patients. Issue 5 (11th December 2017) - Laghi, Franco; Khan, Najeeb; Schnell, Thimothy; Aleksonis, Dinas; Hammond, Kendra; Shaikh, Hameeda; Collins, Eileen; Jubran, Amal; Tobin, Martin J
ABSTRACT: Introduction: In mechanically ventilated patients, nonvolitional assessment of quadriceps weakness using femoral‐nerve stimulation (twitch force) while the leg rests on a right‐angle trapezoid or dangles from the bed edge is impractical. Accordingly, we developed a knee‐support apparatus for use in ventilated patients. Methods: Ninety subjects (12 ventilated patients, 28 ambulatory patients, and 50 healthy subjects) were enrolled. Twitches with leg‐dangling, trapezoid, and knee‐support setups were compared. Results: Knee‐support twitches were similar to trapezoid twitches but smaller than leg‐dangling twitches ( P  < 0.0001). Inter‐ and intraoperator agreement was high for knee‐support twitches at 1 week and 1 month. In ventilated patients, knee‐support twitches were smaller than in healthy subjects and ambulatory patients ( P  < 0.004). Discussion: The new knee‐support apparatus allows accurate recording of quadriceps twitches. The ease of use in ventilated patients and excellent inter‐ and intraoperator agreement suggest that this technique is suitable for cross‐sectional and longitudinal studies in critically ill patients. Muscle Nerve 57 : 784–791, 2018